The Pho4 transcription factor mediates the response to arsenate and arsenite in Candida albicans - Urrialde, Verónica; Prieto, Daniel; Pla, Jesús; Alonso-Monge, Rebeca (Frontiers in Microbiology, 2015)
Arsenate (As (V)) is the dominant form of the toxic metalloid arsenic (As). Microorganisms have consequently developed mechanisms to detoxify and tolerate this kind of compounds. In the present work, we have explored the arsenate sensing and signaling mechanisms in the pathogenic fungus Candida albicans. Although mutants impaired in the Hog1 or Mkc1-mediated pathways did not show significant sensitivity to this compound, both Hog1 and Mkc1 became phosphorylated upon addition of sodium arsenate to growing cells. Hog1 phosphorylation upon arsenate challenge was shown to be Ssk1-dependent. A screening designed for the identification of transcription factors involved in the arsenate response identified Pho4, a transcription factor of the myc-family, as pho4 mutants were susceptible to As (V). The expression of PHO4 was shortly induced in the presence of sodium arsenate in a Hog1-independent manner. Pho4 level affects Hog1 phosphorylation upon As (V) challenge, suggesting an indirect relationship between Pho4 activity and signaling in C. albicans. Pho4 also mediates the response to arsenite as revealed by the fact that pho4 defective mutants are sensitive to arsenite and Pho4 becomes phosphorylated upon sodium arsenite addition. Arsenite also triggers Hog1 phosphorylation by a process that is, in this case, independent of the Ssk1 kinase. These results indicate that the HOG pathway mediates the response to arsenate and arsenite in C. albicans and that the Pho4 transcription factor can differentiate among As (III), As (V) and Pi, triggering presumably specific responses.